Strategic Human Resource Management as a Driver of Organizational Ambidexterity - Arief abdul aziz; Sujoko Sujoko (Oikonomia : Journal of Management Economics and Accounting, 2026)
This article develops a conceptual explanation of how Strategic Human Resource Management (SHRM) acts as a primary driver of organizational ambidexterity by drawing an analogy from research on the social and structural determinants of women’s reproductive health. Health studies consistently show that outcomes are not determined mainly by the presence of medical services, but by contextual factors such as norms, socio-economic conditions, literacy, autonomy, and access that enable individuals to utilize those services effectively. Using this cross-disciplinary insight, the article argues that organizational ambidexterity is not primarily determined by structural design or strategic intent, but by SHRM systems that create enabling conditions for employees to engage in both exploratory and exploitative activities. Employing a conceptual integrative approach, the study maps determinants identified in reproductive health research to their organizational equivalents within SHRM practices and develops a framework positioning SHRM as the contextual architecture that supports ambidexterity. The findings suggest that culture building, empowerment mechanisms, learning systems, access to information, and aligned performance practices are essential HR-driven enablers that allow exploration and exploitation to coexist. The article contributes theoretically by reframing ambidexterity as a human and systemic capability rooted in SHRM, and practically by highlighting the need for organizations to prioritize HR system design alongside technological and structural investments to achieve sustainable performance.